Potential use of collagen extract from sea urchin for wound healing: Potensi penggunaan ekstrak kolagen dari landak laut untuk penyembuhan luka - Ramadhan, Bagas Karunia; Amru, Muh Akmal; Masruroh, Bihaeri Itsna; Ika, Khaerunnisa; Rieuwpassa, Irene E. (Makassar Dental Journal PDGI Makassar, 2024)
Wound healing in oral tissues requires a series of processes to close the wound and prevent infection. Sea urchin (SU) collagen can be utilised in biomedical applications such as periodontal tissue regeneration and wound healing in oral and maxillofacial surgi-cal treatments. Research shows that marine-sourced collagen can promote wound healing and skin regeneration in animals. This paper explores the potential of SU collagen as a biomaterial for wound healing applications in oral tissues. This collagen is sourced from marine connective tissues such as echinoderms and SU. Further research is needed to understand the potential of marine-sourced collagen in wound care and tissue regeneration in humans. The SU collagen shows favourable mechanical properties and potential for sustainable production. The SU collagen is promising for use in wound healing and tissue regeneration especially in oral tissues. It is concluded that SU collagen extract can accelerate wound healing and reduce scar tissue formation.